T2 위암에서 림프절 절제술의 범위에 관한 고찰 - 김완수(Wan Soo Kim); 박성흠(Seong-Heum Park); 김종흥(Jong Heung Kim) (Annals of surgical treatment and research, 2002)
Purpose: Lymph node metastasis is an important prognostic variable in gastric cancer and most locoregional treatment failures are believed to be caused by insufficient nodal clearance. The aim of this study was to determine the clinicopathological features influencing lymph node metastasis, and an appropriate extent of lymphadenectomy, in T2 stage gastric cancer. Methods: A retrospective review of eighty one patients with T2 gastric cancer, treated between 1987 and 1996, was performed, and included survival and statistical analysis to determine prognosticators and variables influencing lymph node metastasis. Results: Lymph node metastasis was found in 36 patients (44.4%, 28 N1, 7 N2 and 1 N3), including 3 that had skipped to the second node group. The rate of lymph node metastasis was significantly higher in the subgroup with lymphatic invasion than in those without invasion (80.0% vs. 36.4%, P=0.002). There were no other clinical parameters for the detection of metastasis in regional lymph nodes. Operative curability was the only significant prognosticator in T2 stage gastric cancer (Relative risk; 7.9337, P=0.0049). Conclusion: There were no clinical parameters for the detection of metastasis in regional lymph nodes in T2 stage cancer, but assessment of the operative curability was very important for predicting the prognosis. For these reasons, radical lymphadenectomy, including at least the second node group, is the standard surgical procedure for gastric cancer in the T2 stage. (J Korean Surg Soc 2002;63:468-472) KCI Citation Count: 2